Buffer Zone Management Impact on Birds Assemblage in the High Nature Value Farmland (HNVf) : a study case on Meru Betiri National Park - Nilasari Dewi; Agung Sih Kurnianto (University of Brawijaya, 2021)
This study aims to analyze the distribution of bird communities and the impact of vegetation on bird habitat preferences in the buffer zone. Research is carried out in agricultural areas in the Buffer zone, Rehabilitation Zone, and on the edge of the plantation. The research location was determined at 37 points: Rajekwesi (4), Sukamade (12), Bandealit (8), Wonoasri (5), Andongrejo (3), Sanenrejo (5). We applied the point count method (r = 17.5 m) in this study, where each point is at least 100-150 meters apart. In the study, 74.6% of records were birds with agricultural specialities and 71.30% of individuals on tree habitats. Birds with specialization in agriculture were found in large numbers related to the protection provided by the TNMB conservation area to bird habitat. Sukamade is the area with the highest number of records. As many as 40.10% were found in tree habitats followed by seedling (16.28%), poles (15.93%), flying over (15.76%), and sapling (11.90%)